The Boneless Mercies - Tucholke, April Genevieve (New York : Farrar Straus Giroux, 2018)
Four female mercenaries known as Boneless Mercies, weary of roaming Vorseland, ignored and forgotten until they are needed for mercy killings, decide to seek glory by going after a legendary monster in this reimagining of Beowulf.
Keywords: Fantasy; Mercenary troops -- Fiction; Euthanasia -- Fiction; Monsters -- Fiction; Mythology, Norse -- Fiction